Erosion protective coatings for low density, highly porous carbon/carbon composites - Smeacetto, F.; Salvo, M.; Ferraris, M.; Casalegno, V.; Canavese, Giancarlo; Moskalewicz, Tomasz; Ellacott, S.; Rawlings, R. D.; Boccaccini, Aldo R. (Carbon, 2009)
A simple and low cost method based on slurry coating was used to produce silicon carbide, titanium carbide and glass-ceramic coatings on low density carbon/carbon composites in order to improve their erosion resistance. Microstructural analyses were performed for substrate and coatings by optical microscopy, and scanning and transmission electron microscopy. As-received and coated composites were submitted to erosion tests using a sandblasting machine according to ASTM G76-95. The best results were obtained with a silica-alumina-yttria based glass-ceramic coating. © 2009 Elsevier Ltd. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2009.tech.IW.LM.erosio